Propuesta de indicadores ecológicos a nivel espacial para el monitoreo de la restauración de paisajes en el norte del cantón Loja - Burneo Rodríguez, Carlos Andrés (2024)
The spatial monitoring of natural landscapes, as part of restoration efforts, allows for the identification of changes in landscapes over time and space. Landscape restoration has become a global priority; however, monitoring landscape quality has grown increasingly important due to the lack of standardized methodologies for tracking progress at the spatial level, which poses a significant challenge. In northern Loja Canton, despite having ongoing restoration projects and an abundance of spatial data, the absence of specific tools to evaluate the effectiveness of restoration interventions through ecological indicators at the spatial level exacerbates this issue. The objective of this research is to propose a set of spatial ecological indicators to monitor landscape restoration dynamics, applicable across different regions of Ecuador. Through a systematic review of scientific literature and bibliometric analysis, a wide range of spatial ecological indicators for restoration monitoring were identified (219). After applying a series of filters, 19 indicators were selected based on their relevance, data availability, and ability to capture changes in vegetation over time. Additionally, the top- performing indicators (NDVI, EVI, AVI) were applied using the Google Earth Engine platform, and their trends over time were analyzed using non-parametric statistical tests (Mann- Kendall). The results of these analyses revealed patterns of vegetation change and provided insights into the effectiveness of restoration interventions. In conclusion, this research contributes to the development of spatial tools and methodologies in remote sensing and geographic information systems for monitoring landscape restoration in tropical regions. The proposed spatial ecological indicators provide a robust foundation for evaluating the success of restoration initiatives, facilitating decision-making for researchers, managers, and administrators to improve the planning and monitoring of restoration projects in Ecuador.